Guardians of Democracy: Exploring the Feasibility and Viability of Organizing Police Task Forces in Philippine Election Hotspot Areas - Angelito M Dangli, Jr (Future Science / FSH-PH Publications, 2026)
Election-related violence is one of the threats to democratic governance. This is evident in some provinces in the Philippines due to intimidation, political competition, and institutional weaknesses. While there have been studies about the issue of security during the election process from the campaign period until the proclamation of winners, no research has discussed what happens after the election. Questions on how inter-agency coordination, witness protection, accountability, and investigation measures continue after the disbandment of election task forces are yet to be answered by the gap in the literature. One of the important issues regarding governance is thus how public safety beyond election day can be maintained effectively. This study sought to investigate the feasibility, effectiveness, acceptability, sustainability, and long-term viability of creating police task forces in election hotspots in the provinces of Abra and Cagayan. Data were collected using qualitative research through key informant interviews and focus group discussions with police investigators, COMELEC field officials, victims, witnesses, and community stakeholders. The data were analyzed using Braun and Clarke’s (2021) Reflexive Thematic Analysis. The findings indicate that police task forces were indeed effective in reducing visible forms of election-related violence through the deployment of additional police personnel, patrols, checkpoints, monitoring of intelligence, and the conduct of police operations, like the implementation of search warrants and arrest of wanted persons. Their sustainability, however, was hampered by witness intimidation, political pressure, lack of coordination among government institutions, and the temporary nature of task-force deployment.